1998
DOI: 10.1017/s0959270900003610
|View full text |Cite
|
Sign up to set email alerts
|

The status and conservation of threatened and near-threatened species of birds in the Red River Delta, Vietnam

Abstract: SummaryThe Red River Delta in northern Vietnam is an important stopover and wintering site for migratory waterbirds. During the spring of 1994, six globally threatened and five near-threatened species were observed in the coastal areas of the Delta. According to current applications of threat categories, one of the species has Critical status (Black-faced Spoonbill Platalea minor), three are Endangered (Nordmann's Greenshank Tringa guttifer, Saunders's Gull Larus saundersi and Chinese Egret Egretta eulophotes)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
3
0
2
Order By: Relevance
“…Based on the ringing and flag resighting records in Guangxi, Yi et al (2023) demonstrated the migration connectivity between the Beibu Gulf and Tasmania in Australia, Chukotka in Russia, and Jiangsu in China. In Vietnam, Xuan Thuy National Park (NP) has been well recognized for its importance to the black-faced spoonbill and spoon-billed sandpiper and has been regularly surveyed since the 1990s (Pedersen and Nielsen, 1998). Besides, there are substantial knowledge gaps in Southeast Asia, including Vietnam (Choi et al, 2016;Yong et al, 2022;Nguyen et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the ringing and flag resighting records in Guangxi, Yi et al (2023) demonstrated the migration connectivity between the Beibu Gulf and Tasmania in Australia, Chukotka in Russia, and Jiangsu in China. In Vietnam, Xuan Thuy National Park (NP) has been well recognized for its importance to the black-faced spoonbill and spoon-billed sandpiper and has been regularly surveyed since the 1990s (Pedersen and Nielsen, 1998). Besides, there are substantial knowledge gaps in Southeast Asia, including Vietnam (Choi et al, 2016;Yong et al, 2022;Nguyen et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…According to Yong et al (2022), Vietnam has 13 coastal Important Bird and Biodiversity Areas (IBAs), supporting 12 threatened bird species. Globally threatened species, such as Saunders's gull Saundersilarus saundersi, have been recorded in the Red River Delta of north Vietnam (Pedersen and Nielsen, 1998), while great knot Calidris tenuirostris and spoonbilled sandpiper were recorded in the Mekong Delta, Southern Vietnam (Zöckler et al, 2016;Nguyen et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Ngoài hệ sinh thái rừng ngập mặn, vùng ĐNN Đồng Rui còn có các hệ sinh thái cửa sông, bãi triều, đầm hồ,... [5]. Khu vực này cùng với hệ thống rừng ngập mặn ven biển Bắc Bộ có nhiều sinh cảnh sống quan trọng và là điểm dừng chân của nhiều loài chim di cư, đặc biệt là các loài chim nước [1], [6]. Dưới tác động của các hoạt động kinh tế, diện tích rừng ngập mặn tự nhiên ở Đồng Rui đã giảm từ khoảng 3.000 ha trước năm 1975 xuống còn 1.523 ha vào năm 2000.…”
Section: đặT Vấn đềunclassified
“…Là vùng đất ngập nước nằm ven biển Vịnh Bắc Bộ -nơi có những điểm dừng chân và trú đông quan trọng của các loài chim nước [1], [6], khu vực rừng ngập mặn Đồng Rui là một trong những nơi trú chân của các loài chim biển và chim di cư. Trong kết quả ghi nhận ban đầu có 37 loài chim nước được ghi nhận trong khu vực thuộc các bộ chim nước điển hình: Ngỗng, Le hôi, Chim điên, Bồ nông, Sếu, Rẽ, Sả.…”
Section: Thành Phần Loài Chim ở Khu Vực đNn đồNg Ruiunclassified
“…Land-use change as a result of aquaculture, energy, infrastructure and residential development, sand mining and land reclamation are the leading drivers of wetland conversion and loss in South-east Asia (Round, 2006; Lim & Posa, 2014; Lai et al, 2015; Jensen, 2018). Aquaculture intensification for fish and prawn farming across coastal South-east Asia, and the expansion of wet paddy cultivation and mega coastal development projects for ports and residential areas have contributed to the widespread reclamation and degradation of mangroves, salt marshes, seagrass beds and mudflats (de Graaf & Xuan, 1998; Richards & Friess, 2016; Rahman, 2017; Jensen, 2018), leading to a loss of habitat for migratory waterbird species (Pedersen & Nielsen, 1998; Buckton & Safford, 2004; Yasue & Dearden, 2009). Over time, coastal erosion, exacerbated by anthropogenic alteration of the sediment regimes of rivers and sea level rise poses a threat to coastal wetlands, especially in the Mekong Delta and the Gulf of Thailand (Duriyapong & Nakhapakorn, 2011; Kuenzer & Renaud, 2012; Marchesiello et al, 2019).…”
Section: Key Challenges For Conserving Coastal Wetlandsmentioning
confidence: 99%